PENDAMPINGAN PENYUSUNAN MODUL AJAR BERBASIS KURIKULUM MERDEKA TERINTEGRASI NILAI MODERASI BERAGAMA PADA GURU BAHASA INGGRIS MADRASAH DI KABUPATEN BENGKULU SELATAN DAN KAUR - Hakim, M. Arif Rahman; Revola, Yashori; Serasi, Reko; Alimi, Adinda Azzahroh Salsabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early observations by the authors to English teachers in madrasahs in all districts and cities of Bengkulu province show that teachers need a lot more training to better understand the Merdeka Curriculum, especially when it comes to making changes to how learning plans are made. This community service program aims to support madrasah teachers in the Bengkulu Selatan and Kaur districts of Bengkulu province through training focused on the development and technical preparation of teaching modules aligned with the independent curriculum and incorporating the values of religious moderation. This community service employs Participatory Action Research (PAR) as its approach. The outcomes of this community service initiative have been positive, as evidenced by participant feedback and engagement. Participants expressed satisfaction with the training and support provided in developing teaching modules, which are essential for enhancing the innovative and engaging teaching and learning process in the context of the independent curriculum. The attendance of participants during the course exceeded 100%, reflecting their tremendous excitement. In conclusion, the Community Service (PKM) initiative, which created teaching modules for English subjects in madrasas and combined them with religious moderation based on an independent curriculum, was a success. It had direct effects and implications for the English teachers in madrasas who were targeted by the PKM program.